High seroprevalence of anti‐Hepatitis E antibodies in Austrian patients with autoimmune hepatitis. (20th December 2018) - Eder, Michael; Strassl, Robert; Beinhardt, Sandra; Stättermayer, Albert Friedrich; Kozbial, Karin; Lagler, Heimo; Holzmann, Heidemarie; Trauner, Michael; Hofer, Harald
Abstract: Background & Aims: Increasing numbers of autochthonous hepatitis E virus infections have been reported in Europe. Chronic infections have been shown in immune‐compromised patients after solid organ transplantation. Hepatitis E virus might be a possible trigger for autoimmune hepatitis and might cause disease flares or relapses in the further course of disease. Aim of this study was to investigate the presence of hepatitis E virus antibodies and hepatitis E virus RNA, and to analyse their impact on immunosuppressive treatment in patients with autoimmune hepatitis. Methods: Sera from 92 autoimmune hepatitis patients (73/79.3% female, age: 42.2 ± 16.3 years [mean ± SD]) were tested. Patients were scored according to the simplified and revised scoring systems of the International Autoimmune Hepatitis Group. The prevalence of anti‐ hepatitis E virus antibodies (Beijing Wantai Biological Pharmacy Enterprises Co., Ltd, Beijing, China) and hepatitis E virus RNA was determined. Results: 19/20.7% autoimmune hepatitis patients tested positive for hepatitis E virus‐IgG, which was higher than in previous reports of healthy Austrian individuals (12.4%, P = 0.031); hepatitis E virus RNA was not detectable in any patient. Anti‐hepatitis E virus positive patients were older (49.5 ± 9.5 vs 40.4 ± 17.2 years [mean ± SD], P = 0.033) but did not differ in laboratory findings at diagnosis (AST: 14.6 [1.3‐70.6] vs 9.5 [0.7‐62.7] × ULN [median/range]; P = 0.387, alanine aminotransferase: 18.3 [1.6‐62.7] vs. 12.9 [0.8‐62.6] × ULN; P = 0.511; IgG: 1.4 [1.0‐2.5] vs 1.3 [0.6‐3.8] g/dL × ULN; P = 0.278) nor in alanine aminotransferase levels after six months (0.7 [0.5‐2.4] vs 1.0 U/L × ULN [0.1‐22.4]; P = 0.077). Conclusions: No chronic hepatitis E virus infection was observed in our cohort of autoimmune hepatitis patients. Anti‐ hepatitis E virus‐IgG positive patients were older and the seroprevalence was nearly twice as high as reported previously in healthy Austrian individuals, suggesting that hepatitis E virus‐infection might act as trigger for the development of autoimmune hepatitis.